The aesthetics of the S17 expressway - Kowal, Maciej (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The article describes the aesthetic aspects of the S17 expressway. The paper presents two, adjacent to each other S17 sections, “Kurów Zachód” - “Jastków” and “Jastków” - “Lublin Sławin”. Author’s aesthetic feelings regarding projects executed by various design offices were presented. The expressway plan and profile shape and engineering design solutions were described.